ANALISIS KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK SEKOLAH MENENGAH ATAS NEGERI DI KOTA MAKASSAR - Muh. Tri Prasetia Nua; Abdul Haris (SEMINAR NASIONAL DIES NATALIS 62, 2023)
This study aims to describe the critical thinking skills of students in Physics subjects. The subjects of this study were students of class XI MIPA in public high schools in Makassar city. This type of research is descriptive quantitative survey method. The instrument used in this research is an essay form question. The results showed that the critical thinking skills of students in solving physics problems were 75.50% of the total population of students in the low category. In addition, the comparison of critical thinking skills of female students is higher than male students. It can be concluded that the critical thinking skills of high school students in Makassar city are still low.